Multilevel Encryption of Messages for Secured Communication - R., Krishnaja.; R., Parameswaran. (International Journal of Engineering and Technology, 2018)
The security of information passed through the communication channel has become a major concern. Encoding of the messages before transmitting through the channel is most vital. We propose a three level encryption (encoding) using musical notes in traditional Indian and Western system as well as the American Standard Code for Information Interchange (ASCII). A unique method for the decryption is also mentioned in the paper.Â Â